Transcultural Migration in the Novels of Hédi Bouraoui : A New Ulysses - Sabiston, Elizabeth Jean (Francopolyphonies Ser, 2020)
Intro -- Contents -- Chapter 1 Introduction -- Chapter 2 Hédi Bouraoui's Cap Nord: Mythopoeia and the Quest for Language -- 1 North and South: the New Hannibal -- 2 A Ulyssean Quest -- 3 Islands and the Quest for Language -- 4 Female Mentors: Saadia and Safia -- 5 Albert Lacouture and Tante Souad: Written and Folkloric Traditions -- 6 Manhattan Island: English and the New World -- 7 Voices from Beyond the Grave: Father and Mother -- 8 Sardinia: the Journey Begins -- 9 Descent into the Underground -- 10 Women and Islands -- 11 A Storytelling Festival -- 12 Sicily: the Crossroads -- 13 Mama Lucia and the Word of the Father -- 14 A Return and a New Departure: towards the Mother -- Chapter 3 Penelope Liberated: the Female Quest in Les Aléas d'une Odyssée -- 1 Part 1 Corsica: the Mother Discovered -- 1.1 Return to Origins -- 1.2 Corsica: Mothers and Muses, True and False -- 1.3 Mentors: the Personal and the Political -- 1.4 The Ending: "Levons l'ancre" -- 2 Part 2 Le Dit de Pénélope: Laura at the Helm -- 2.1 Crete: Muses, Mothers, Mentors, Monsters, and Gods -- 2.2 The House of Kitzikis -- Chapter 4 Adventures of a Young Man: the Initiation of Télémaque in Méditerranée à voile toute -- 1 Première Partie: Hanniballade à Majorque -- 1.1 Hannibal in Mallorca: Microcosm and Macrocosm -- 1.2 Hannibal's Epiphany or "Illumination" -- 1.3 Hannibal and Dolorès: "He Said, She Said" -- 1.4 Laura Takes Command -- 1.5 The Detective Story: Inès's Kidnapping -- 2 Deuxième Partie: Le Marcheur de Malte: Télémaque Takes the Reins -- 2.1 Malta: Prologue in Paris -- 2.2 Malta: Center of the Mediterranean -- 2.3 Love and History: the Legends of Malta and the Fat Lady -- 2.4 The Wisdom of the Aged -- 2.5 Walking and Reading: Mens Sana in Corpore Sano -- 2.6 Gozo: Calypso's Isle -- 2.7 The Carnival: a Bakhtinian Celebration.